IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER SISWA - Kelvin Bastari (UNISAN JURNAL, 2024)
Character education is seen as subordinate to noble morals. Historical facts confirm that the concept of character is profane. However, character education in Indonesia cannot be separated from religion, because the Unitary State of the Republic of Indonesia is based on Pancasila, especially, the First Principle, Belief in One Almighty God. The important things about the components that form character itself consist of: religiousness, honesty, tolerance, discipline. , hard work, creative, independent, democratic, curious, national spirit, love of the country, respect for achievements, friendly/communicative, love of peace, likes to read, cares about the environment, social care and responsibility. This research is a qualitative descriptive research. Research data was collected through observation, interviews and documentaries. Positive Student Behavior: So that character education can be realized well, efforts are made to overcome these obstacles, including: increasing discipline, providing learning facilities and infrastructure, teachers using various methods to arouse student interest and building buildings for religious practices. Discipline is a factor that supports success in improving the quality of education, providing learning facilities and infrastructure Keywords: Management Implementation, character